Carbon Dynamics in Various Agroforestry Systems: A Study of Agrosilvopastural and Two Types of Agrosilvikultural Systems - Wafiqah, Hidayatul; Widjajani, Bakti Wisnu; Wijayanti, Fitri (BIOEDUSCIENCE, 2025)
Background: Global climate change significantly affects carbon dynamics in perennial crop ecosystems, including agroforestry systems. This study aims to analyze carbon dynamics in three types of agroforestry systems: agrosilvopastoral, agrosilvicultural based on horticultural crops, agrosilvicultural based on woody plants, and to identify the diversity and types of vegetation. Methods: The study was conducted from January to March 2025 using field surveys and purposive sampling in Wonosalam, East Java, Indonesia. Laboratory analyses included physical properties (soil texture and bulk density), chemical properties. Results: The regression model showed R2 =0,419 Idicating that 41,9% of soil orgnaik carbon variation is explained by plant biomass carbon stock, highlighting its significant contribution to soil carbon accumulation. Conclusions: The agrosilvicultural system based on woody plants provides the highest contribution to carbon dynamics compared to other types of agroforestry, due to its vegetation composition dominated by woody and perennial plants. The even distribution of the Importance Value Index (IVI) reflects a stable and balanced ecosystem, as observed in plot 3, where excelsa coffee (Coffea excelsa) has an IVI of 37.78%, Durian (Durio zibethinus) has 35.56%, and banana (Musa spp) also has 37.78%. Keywords: Agroforestry; Biomass; Carbon Dynamics